ANALISA TUNGKU PEMBAKARAN ARANG UNTUK MENINGKATKAN PRODUKTIVITAS KARBONISASI ARANG - mohd zulkarnain (Machine : Jurnal Teknik Mesin, 2020)
Charcoal is a residue that is solid in the form of wood burning under controlled conditions. The process of burning is burning wood with limited air, and can produce charcoal, tar, acetic acid, wood alcohol, and wood gas (CO2, CH4, CO, and H2). The purpose of this research is to find out the causes of non-carbonized charcoal, to produce maximum charcoal combustion, and to find out what percentage is charcoal and ash. The case study of this research is a dome-shaped charcoal furnace with a capacity of 4.5 tons owned by one of the indigenous tribesmen who produce wood charcoal, which is located on the main road of Jangkang, Gg native tribe, Bantan District, Bengkalis Regency. The method used in this research is the experimental method and the Slovin method. Because what is varied in this study is the base used, by adding an iron plate and a temperature measuring instrument, namely a thermometer. Data retrieval is done by burning twice to get the comparison results. From the results of research that has been done, it can be explained that in order to obtain maximum charcoal, several factors must be considered, namely temperature, carbonization duration, winding down of doors and chimneys, and closing of combustion doors. second combustion using a plate base two days faster than the first combustion. But the furnace temperature is unstable, there is charcoal that is not carbonized.